Water deficit modifies the carbon isotopic composition of lipids, soluble sugars and leaves of Copaifera langsdorffii Desf. (Fabaceae) - Silva Bertholdi, Angelo Albano da [UNESP]; Costa, Vladimir Eliodoro [UNESP]; Rodrigues, Angelica Lino [UNESP]; Rolim de Almeida, Luiz Fernando [UNESP] (Soc Botanica Brasil, 2018)
Water deficit is most frequent in forest physiognomies subjected to climate change. As a consequence, several tree species alter tissue water potential, gas exchange and production of carbon compounds to overcome damage caused by water deficiency. The working hypothesis, that a reduction in gas exchange by plants experiencing water deficit will affect the composition of carbon compounds in soluble sugars, lipids and vegetative structures, was tested on Copaifera langsdorffii. Stomatal conductance, leaf water potential, and CO2 assimilation rate declined after a period of water deficit. After rehydration, leaf water potential and leaf gas exchange did not recover completely. Water deficit resulted in C-13 enrichment in leaves, soluble sugars and root lipids. Furthermore, the amount of soluble sugars and root lipids decreased after water deficit. In rehydration, the carbon isotopic composition and amount of root lipids returned to levels similar to the control. Under water deficit, C-13-enriched in root lipids assists in the adjustment of cellular membrane turgidity and avoids damage to the process of water absorption by roots. These physiological adjustments permit a better understanding of the responses of Copaifera langsdorffi to water deficit.
Keywords: carbon assimilation; carbon isotopic composition; lipids; soluble sugars; water deficit